2011
DOI: 10.1158/1078-0432.ccr-10-2547
|View full text |Cite
|
Sign up to set email alerts
|

Modulators of Arginine Metabolism Do Not Impact on Peripheral T-Cell Tolerance and Disease Progression in a Model of Spontaneous Prostate Cancer

Abstract: Purpose: Chronic inflammation, recruitment of myeloid-derived cells, and perturbation of the arginine metabolism have been all proposed as mechanisms favoring prostate carcinogenesis and tumor immunoescape. Objective of this study was to evaluate whether accumulation of CD11b þ Gr1þ cells, also defined myeloid-derived suppressor cells, occur in mice affected by transplantable or spontaneous prostate cancer (PC). We also investigated whether N(G) nitro-L-arginine methyl ester (L-NAME) and sildenafil, both modul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…Indeed, CSC and/or other more differentiated tumor cells may generate immunosuppressive networks within the primary lesion, and anergic Tag-specific CD8 þ T cells are found in the prostate of TRAMP mice (14). Both regulatory T cells and myeloid-derived suppressor cells accumulate in the prostate of cancer patients and TRAMP mice, although their targeting revealed insufficient for breaking T-cell tolerance and sustaining antitumor immunity (46,47). Moreover, in TRAMP and in human prostate cancer lesions, a population of tolerogenic DCs induces CD8 þ T cells to acquire suppressive functions through indoleamine-2,3-dioxygenase, arginase, TGFb, and PDL-1 (48).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CSC and/or other more differentiated tumor cells may generate immunosuppressive networks within the primary lesion, and anergic Tag-specific CD8 þ T cells are found in the prostate of TRAMP mice (14). Both regulatory T cells and myeloid-derived suppressor cells accumulate in the prostate of cancer patients and TRAMP mice, although their targeting revealed insufficient for breaking T-cell tolerance and sustaining antitumor immunity (46,47). Moreover, in TRAMP and in human prostate cancer lesions, a population of tolerogenic DCs induces CD8 þ T cells to acquire suppressive functions through indoleamine-2,3-dioxygenase, arginase, TGFb, and PDL-1 (48).…”
Section: Discussionmentioning
confidence: 99%
“…MDSCs accumulate in the tumor microenvironment as well as the blood, lymph nodes, and bone marrow in association with several forms of human cancer and may contribute to tumor immune escape due to their general functional role in immune suppression (Ostrand-Rosenberg and Sinha 2009). In regard to prostate cancer, multiple murine models of prostate cancer demonstrate accumulation of MDSCs in tumors along with a potential contribution to tumor progression (Wu et al 2012;Svensson et al 2011;Rigamonti et al 2011). …”
Section: Additional Innate Immune Cells In Prostate Cancermentioning
confidence: 99%
“…TRAMP-C1 mouse tumor cell lines were maintained as previously described (18). MCA.WT100-5 and MCA.WT100-7 cells were derived from WT mice that had been inoculated with 100 mg of 3-methylcholanthrene (MCA).…”
Section: Cell Lines and Antibodiesmentioning
confidence: 99%
“…Previous studies suggested that CD73 is associated with malignant transformation of prostate epithelial cells (20). TRAMP transgenic mice develop mild to severe prostate hyperplasia by 12 weeks of age and by 24 weeks of age, approximately 100% of male mice have poorly differentiated and invasive adenocarcinomas (18). We generated CD73 À/À TRAMP transgenic mice and compared prostate weights with CD73 þ/þ TRAMP mice.…”
Section: Cd73 Promotes Prostate Cancer In Tramp Transgenic Micementioning
confidence: 99%